UK multisite evaluation of the impact of clinical educators in EDs from a learner's perspective. Issue 8 (8th June 2021) - Hemavathi, Muniswamy; Huynh, Chi; Phillips, Eloise; Aiello, Matthew; Kennedy, Brian; Clancy, Mike; Hamer, Wayne; Rutherford, Graham; Khan, Aanika; Terry, David
Abstract : Background: In England, demand for emergency care is increasing while there is also a staffing shortage. The Royal College of Emergency Medicine (RCEM) suggested that appointment of senior doctors as clinical educators (CEs) would enable support and development of learners in EDs and improve retention and well-being. This study aimed to evaluate the impact of CEs in ED on learners. Methods: CEs were placed in 54 NHS Acute Trust EDs for a pilot beginning July 2018 and ending October 2020. Learners from multiple disciplines working at 54 NHS Acute Trust EDs where CEs were deployed were invited to complete an online survey designed to identify the impact of CEs in July of 2019, as part of an interim service evaluation. Results: Respondents numbered 493 from 49 of 54 study sites, including 286 (58%) medical (non-consultant) and 72 (14.6%) all other nursing, allied health professionals. 9 out of 10 learners reported having experienced a change to their learning as a result of the deployment of CEs in their department. 49.9% (246/493) reported that CEs had a positive impact on their well-being. 95% (340/358) reported an improved accessibility to undertaking clinical based assessments. 78% (281/358) perceived that access to CEs increased likelihood of passing assessments. Of those responding, 80.9% (399/493) reported they would remain/return to the same ED with a CE, and 92.5% (456/493) responded that they would prefer to go to a Trust with a CE. Conclusions: According to survey respondents, deployment of CEs across NHS Trusts has resulted in improvement and increased accessibility of learning and assessment opportunities for learners within ED. The impact of CEs on well-being is uncertain with half reporting improvement and the remaining half unsure. Further evaluation within the project will continue to explore the service benefit and workforce impact of the CEED intervention.